THE EFFECT OF COMBINATION BETWEEN ACUPRESSURE AND SELF HYPNOSIS IN OVERCOMING ADOLESCENT DYSMENORRHEA - Karuniadi, I Gusti Agung Manik; Widiastini, Luh Putu; Saraswati, Putu Ayu Dina (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2024)
Dysmenorrhea is a disorder that occurs during menstruation which most often causes teenagers to go to health services for consultation and treatment. Self Hypnosis and acupressure are simple nonpharmacological therapies that can be done independently by teenagers to treat dysmenorrhoea. The aim of this research is to determine the effect of Keris (a combination of acupressure and self-hypnosis) in overcoming adolescent dysmenorrhoea at SMPN 2 Abiansemal. This research uses quantitative, preexperimental research methods with a one group pretest-posttest design. The instrument used to measure pain in this study was the NRS. The population and sample in this study were teenage girls at SMPN 2 Abiansemal who experienced dysmenorrhoea with a sample size of 38 people. The sampling technique in this research is purposive sampling. This research was carried out in May – August 2023. Bivariate data analysis used Wilcoxon. The research results obtained a p value of 0.000 (<0.05). The average pain value before the intervention was 5.1, it decreased after the intervention was given, as seen from the average pain value after the intervention, namely 3.68. These results indicate that Keris (a combination of acupressure and self-hypnosis) is effective in overcoming adolescent dysmenorrhoea at SMP N 2 Abiansemal.